Analysis of External and Internal Disorder to Understand Band‐Like Transport in n‐Type Organic Semiconductors. Issue 13 (25th February 2021) - Stoeckel, Marc‐Antoine; Olivier, Yoann; Gobbi, Marco; Dudenko, Dmytro; Lemaur, Vincent; Zbiri, Mohamed; Guilbert, Anne A. Y.; D'Avino, Gabriele; Liscio, Fabiola; Migliori, Andrea; Ortolani, Luca; Demitri, Nicola; et al.
Abstract: Charge transport in organic semiconductors is notoriously extremely sensitive to the presence of disorder, both internal and external (i.e., related to interactions with the dielectric layer), especially for n‐type materials. Internal dynamic disorder stems from large thermal fluctuations both in intermolecular transfer integrals and (molecular) site energies in weakly interacting van der Waals solids and sources transient localization of the charge carriers. The molecular vibrations that drive transient localization typically operate at low‐frequency (<a‐few‐hundred cm −1 ), which makes it difficult to assess them experimentally. Hitherto, this has prevented the identification of clear molecular design rules to control and reduce dynamic disorder. In addition, the disorder can also be external, being controlled by the gate insulator dielectric properties. Here a comprehensive study of charge transport in two closely related n‐type molecular organic semiconductors using a combination of temperature‐dependent inelastic neutron scattering and photoelectron spectroscopy corroborated by electrical measurements, theory, and simulations is reported. Unambiguous evidence that ad hoc molecular design enables the electron charge carriers to be freed from both internal and external disorder to ultimately reach band‐like electron transport is provided. Abstract : Molecular vibrations govern the charge transport in organic semiconductors, which is limited by different sources of disorder. Understanding and mastering the disorder in these materials can drive the design of better semiconductors featuring band‐like transport.